Rancang Bangun Absensi Karyawan Verifikasi Foto Selfie Dengan Global Positioning System Menggunakan Metode Prototype - Pamudi Pamudi; Yudi Kristyawan; Arif Nur Hasan; Hengki Suhartoyo; Mochammad Syaiful Riza (SPIRIT, 2023)
Abstract: Employee attendance is an attendance data collection process which is an important performance appraisal for a company engaged in software and information technology consulting. Companies that still use manual attendance are of course very unfortunate if in this digital era they do not take advantage of increasingly sophisticated technology. In this case, many employees continue to falsify manual attendance data which is detrimental to the company and hinders its progress. Using a manual attendance system also has a lot of risks and takes a lot of time because you have to record the attendance of each employee. Therefore, the authors created a selfie photo employee attendance system with GPS that can detect whether the employee taking the attendance is in the office area or not. with a radius of 200 meters from the office point. With the employee attendance application, it can help companies in not controlling employee work time and helping managers to find out which employees are absent in the office and not every day. Respondents' assessment of the employee attendance application acceptance test obtained the percentage of the SB rating category by 34%, B by 48%, C by 14%, and K by 4%. From this assessment it can be concluded that the application made is acceptable to respondents and this application can help employees and company directors for employee attendance based on selfie photos with a radiusÂ Â